Efecto de diferentes dosis de fertilización mineral sobre la respuesta productiva del cultivo de banano en el cantón Machala - Huarquila Henriquez, William Andres (2017)
The cultivation of bananas in the province of El Oro and even more in the banana capital of the world is one of the economic engines of the southern region of the country, in turn is the pillar of the development of the tropical countries that are dedicated to this crop. The banana produced in Ecuador, which has European, American and Asian countries as demanded by its quality in the fruit compared to its competition. Costa Rica, the beneficial geographical position of Ecuador makes our country an excellent aptitude for the exploitation of the Cultivation, generating about 3.8% of the total PIB and 50% of the national agricultural PIB, the soils where banana is produced in Latin America helped determine the fertilization rates of the crop, since banana is one of the most extractive crops of Nutrients of the soil, because of these fertilization recommendations consider the nutrient demand, the stage of development of the crop with the respective availability in the soil. This research was carried out in order to compare the different levels of potassium nitrate (KNO3) mineral nutrition applied in a commercial banana crop and to establish the differences between the productive parameters, including yield and morphological parameters Cultivation, the place where it was carried out was in a conventional farm New Era located in the Primavera Sector Machala Canton dedicated to this crop in which we delimited an area for the investigation in which the experiment was developed whose dimensions per plot were of 9 meters The total number of plots was 25 for having five treatments and five replicates, the total experimental area was 3375 square meters, the treatments were: T1 (absolute control without application of fertilizers), T2 (Fertilization Of the conventional farm on a potassium sulfate basis), T3 (100% recommended fertilization rate based on potassium nitrate KNO3), T4 (125% recommended fertilization based on KNO3 potassium nitrate), T5 (75% Of the recommended dose of fertilization with potassium nitrate KNO3), the agronomic management of the experimental plots was the same except in the fertilization, which was supplied on the day of application the different respective doses to each treatment, the morphological variables such as height Of the plant, perimeter of the pseudotallo, and number of leaves, were taken weekly until the day of flowering of each experimental unit were left to take these variables to proceed to the production variables such as ratio in number of boxes per hectare And the productive yield in tons per hectare being the most important of all. The design of the experiment was completely randomized blocks with five replicates, for statistical analysis we used non-parametric tests since the data did not follow a normal distribution, the results indicate that T3 (100% recommended fertilization-based nitrate Of potassium KNO3) in most of the productive variables is completely different from the others and in morphological variables, the time in weeks from flowering to harvest T3 (100% of recommended fertilization rate based KNO3 potassium nitrate) was different from the other variables, there were no significant differences between the treatments studied.